Community perception and attitude towards sustainable tourism and environmental protection measures: An exploratory study in Muscat, Oman - Anitha Ravikumar; Sheikha Al Subhi; Krishna Murthy Meesala (Economies, 2022)
Sustainable tourism supports a great level of tourist contentment and assures a significant experience for the visitors, realizes the importance of sustainability issues and encourages sustainable tourism practices and customs among them. Long-term success in tourism is possible only with the support of the local residents. Earlier research supports the significance of local population backing in order to make tourism more sustainable. As a result, it is necessary to comprehend the attitudes and perception of the local people, which will provide a treasured acquaintance for numerous tourism improvement programs. The present study was conducted in Muscat, Sultanate of Oman, to understand the community perception on tourism impact and environmental protection measures taken by the government. The study indicates that the local community is aware of the benefits of tourism development. The government should take steps to create awareness about the need for public support for the preservation of heritage sites. They should also be provided information about how the local community can benefit by way of job opportunities, small businesses, etc.
Keywords: 330; attitude; economic; environment and sustainable tourism; keyword; perception; socio-cultural